Occupational Balance Improves Subjective Health and Quality of Life Family with Mental Health Disorders - Mashudi, Sugeng; Sansuwito, Tukimin bin; Purwaningroom, Dian Laila; Pradani, Fitayani Intan (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Occupational Balance (OB) is an important determinant of subjective health and quality of life. This study aimed to examine occupational balance's impact on subjective health and quality of life in families with schizophrenia. Methods: We examined data from 60 adults over the age of 45. Results: Although the effect size was small to medium, OB was identified as an important factor. Independent variables influence subjective health while quality of life variables in the final model, either directly or indirectly. Conclusions: Our findings indicate that promoting better occupational balance can improve subjective health and quality of life. Further research in developing intervention programs based on occupational balance is needed to confirm the feasibility of the intervention and its effects on subjective health and quality of life of family members with schizophrenia.